Solar Photovoltaic Energy and Electricity Security on ECOWAS Countries. (27th August 2017) - Lawin, Emmanuel Agnidé; Bazyomo, Serge Dimitri; Ouedraogo, Abdoulaye
Abstract : The study presented in this paper analyzes the role that photovoltaic energy can play in enhancing energy self-sufficiency in each of the fifteen Economic Community of West African States (ECOWAS) countries. For this purpose, the satellite CM-SAF database, Global Land Cover data and land slope computed from Digital Elevation Model data, was used to compute the area of suitable lands, the potential of energy, and the coefficient of variation of solar irradiation. The results show that 31.76% of the total area of each ECOWAS country has the potential to shelter photovoltaic energy system generators. Except Cape-Verde which lacks data concerning land cover, all the countries of the community dispose of suitable area for photovoltaic systems installation. Using only 1% of these areas at each country scale the amount of the whole community energy production can reach up to 7782.37 TWh·year −1 . The result of solar resource repartition shows that the energy could have a low interannual variation. But, in the same year, a significant variation of solar irradiation exits between months.